The failure of Obama-Netanyahu’s Two-State solution 2009-2016 in the light of waltz theoretical framework - Mimi Nur Atifah Ahmad Daud; Asmady Idris; Asri Salleh (Penerbit Universiti Kebangsaan Malaysia, 2020)
Israel-Palestine conflict is one of the longest conflicts in the world. Since World War II, the United States has always been the main mediator in this conflict. Although the United States had always played a major role in bringing both parties into the negotiating table, it was rather odd during Barack Hussein Obama’s administration (2009-2016). The peace negotiation was rather slow. In fact, it remained stagnant during most of Obama’s administration as opposed to his predecessors. One of the main reasons was due to Obama and Benjamin Netanyahu’s tense relationship. The main objective of this paper is to identify and assess the factors that influenced both individuals’ leadership that resulted in the failure of the Two-State solution. To answer this, the study employs the level of analysis concept propounded by Kenneth N. Waltz (1959, 2001). According to Waltz, this level of analysis includes three images of the international system. They are systemic level, nation-state level and individual level (individual decision). Combined, these levels can exert a strong influence on the leaders’ decision making and behaviour. This study found aggressive characters of both leaders, different interpretations on the Two-State solution (individual level), pressure coming from the domestic level (nation-state level) and the Iranian nuclear programme issue (systemic level) had affected the relationship of both leaders.